2017
DOI: 10.1111/febs.14343
|View full text |Cite
|
Sign up to set email alerts
|

The roles of CSFs on the functional polarization of tumor‐associated macrophages

Abstract: Macrophages have a central role in numerous physiological processes, such as immune defense, maintenance of tissue homeostasis, wound healing, and inflammation. Moreover, in numerous severe disorders, such as cancer or chronic inflammation, their functions can be profoundly affected. Macrophages continuously sense their environment and adapt their phenotypes and functions to the local requirements; this process is called plasticity. In addition to stress signals, metabolites, and direct cell‐contact interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 157 publications
(271 reference statements)
2
108
0
Order By: Relevance
“…Another known stimulus for M1 macrophages is GM-CSF (Granulocyte Macrophage Colony-Stimulating Factor). It activates STAT5, which leads to the activation of the PI3K-AKT pathway (Jeannin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another known stimulus for M1 macrophages is GM-CSF (Granulocyte Macrophage Colony-Stimulating Factor). It activates STAT5, which leads to the activation of the PI3K-AKT pathway (Jeannin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…M-CSF (Macrophage Colony-Stimulating Factor) and IL-34 also induce a M2 phenotype. M-CSF and IL-34 express the same receptor named CD115 and activate the MAP kinases signaling pathway (Jeannin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, despite a significant increase in medullary concentration of IFN-γ in patients with ICMP, its level was not directly associated with the percentage of individual monocyte subpopulations in BM. Apparently, IFN-γ influences monocytopoiesis indirectly, which is further substantiated by the observed correlations between the concentration of M-CSF, a specific inducer of monocytopoiesis, (23) and levels of IFN-γ and other medullary cytokines. Concentrations of M-CSF in BM of patients without ICMP correlated positively to the levels of IL-1β (r=0.62; P<0.01), TNF-α (r=0.60; P<0.01), and IFN-γ (r=0.72; P<0.05).…”
Section: Resultsmentioning
confidence: 73%
“…However, the efficacy of PD-1/PD-L1 inhibitors revealed incompletely definite in patients with various objective response rates, indicating the importance of characterizing tumor immune environment. Previous studies already reported that overall survival (OS) (15) and prognosis in patients could be influenced by fractions of immune environment, including tumor-associated macrophage (16,17), mast cells, or stromal cells. Nevertheless, immune gene biomarkers discovered based on large samples were less reported and characterization of immune signature in tumor microenvironment was of significance for our understanding on ccRCC.…”
mentioning
confidence: 99%